Pendampingan Penyusunan Rencana Anggaran Belanja (RAB) dan Laporan Keuangan Pada Amal Usaha Muhammadiyah Lamongan - Elok Vilantika; Rahmat Agus Santoso (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Based on Law no. 12 of 2012 concerning Higher Education, the Internal Quality Assurance System (SPMI) process should be carried out at least once a year. Currently, the quality and managerial system at one of the charities of Muhamamdiyah Lamongan is still not very good. Organizational management is already running but not in accordance with the desired national university standards. Many things are still done manually and have not been synergized properly. This service aims to help partners become quality universities and can compete with other universities. This service activity is also expected to bring changes to the management system, especially in the financial sector so that it is arranged according to university standard rules. The service team will provide explanations regarding national university standards and ways to achieve perfect quality so that they can get excellent or even superior accreditation scores. The method used in this service is to provide assistance and workshops related to the management of the financial system. The results of the training provide benefits, namely the creation of a good financial system in accordance with National Higher Education Standards and improving the quality of higher education as a whole.